Wealth accumulation and inequality: the drivers of intra-racial wealth inequality in South Africa - Mthimkhulu, Mbalenhle Rachel (My University, 2021)
South Africa is the most unequal country in the world according to the World Bank. Though between race inequality has been decreasing, albeit still high, within race inequality has been increasing. This paper investigates the determinants of individual within group wealth inequality in South Africa using National Dynamic Household Data (NIDS) Wave 5. The individual wealth variable is transformed using the inverse hyperbolic sine (IHS) to deal with skewness and its other unique characteristics. The impact of chosen variables-education, marital status, gender, age and inheritance-on wealth inequality is investigated using Ordinary Least Square (OLS) and Quantile Regression as methods of estimation. The study finds that factors such as gender and education have a significant effect on within race wealth inequality in South Africa
A research report submitted to the School of Economics and Finance, University of the Witwatersrand in partial fulfilment of the degree Master of Commerce (Applied Development Economics), 2021